A Comparative Analysis of Performance of Islamic and Conventional Unit Trusts in Malaysia - Abdullah, Fikriyah (2003)
The investment management of the Islamic funds is based on the syariah principles, meanwhile the conventional funds are not restricted to any principles. Hence, the performance of the Islamic funds and conventional funds may have a significance difference. Moreover, the economic condition may influence or have some implications on the performance of both funds. The study analyzed 65 unit trust funds as the sample of the study. Monthly data were collected over the ten-year period starting from January 1992 up to December 2001 . The measure of performance applied in this study includes the non risk-adjusted performance measures, risk-adjusted performance measures and the measurement of risks. Apart from that, Treynor and Mazuy model was also used to measure the funds managers' selection and market timing ability. The findings revealed that over the ten-year period, the performance of the Islamic funds and the conventional funds are equally well. However, both funds underperformed the market but it is not statistically significant (which have not been tested in previous studies). The performance of the funds was influenced by the economic condition. During the economic crisis, the market was badly affected as compared to unit trust funds, hence the funds outperformed the market (however, statistically it is not significant). Islamic funds performed better during bearish economic trend, while the conventional funds showed better performance during bullish economic period. The findings indicate that the Islamic funds have lower risks as compared to the risk associated with the conventional funds. However, the differences are not statistically significant. Besides that, conventional funds have a marginally better diversification level than the Islamic funds, although both funds were unable to achieve at least 50% market diversification level. The findings also summarized that both funds managers have poor selection and market timing ability as the values of a and y are negative. The result implies that funds managers are unable to correctly identify good bargain stocks and also to forecast the price movements of the general market.